Use of AUV with side scan sonar embedded to testify targets in anchoring areas - Pimentel, Vitor B.; Florentino, Christopher; Nascimento, Guilherme Antonio G. [UNESP]; Carvalho, Rodrigo C. (My University, 2018)
The updating of hydrographie information is crucial to provide credibility to the national nautical documents. This is feasible due to the efforts on the improvement methods and technologies geared to the hydrographic surveys practices and nautical cartographic sciences. In this sense, there is an increasing number of researches exploring the use of Autonomous Underwater Vehicle (AUV) in ocean mapping activities. This equipment, with sensors such as Side Scan Sonar (SSS) embedded, is capable to carry out the imaging, ensonification, dimensioning and acquirement of oceanographic data in an autonomous and simultaneous way, through predetermined AUV parameters. Its application allows the data collection on areas with hard access characteristics, which caters a higher security conditions for the survey vessels, but still preserves the information quality. Moreover, the SSS associated to the AUV enables a closer scanning of the seabed. This sensor generates a better representation of the underwater features as well as a high accuracy on angular and distance disambiguation. This sort of operation aims to correlate objects detected on the seafloor to current information on nautical charts. Thus, it would be possible to testify the existence of a target previously reported. In this sense, concerning about the navigation safety, stands out the acknowledge of the submarine ground in anchoring areas. Therefore, the present fieldwork had as object of research the anchoring area number 2, a section reserved for warships, located inside the Guanabara Bay (Rio de Janeiro-RJ), next to the Brazilian Navy Graduating School (Villegagnon Island). On that zone, an investigation was conducted in order to verify the presence of submarine features pointed by Notice to Mariners to the Nautical Charts 1511 (4th ed., 2000) and 1512 (4th ed., 2000) and reported in the Bathymetric Database of the CHM (Brazilian Navy Hydrographic Center). The AUV system used was the Remus 100S, equipped with an interferometric side scan sonar, operating at a frequency of 100-500 KHz and an MSTL Side Scan Sonar, at a frequency of 900 KHz. The reference data, extracted from the Bathymetric Database of the CHM, were acquired by an EM3000 multibeam echosounder during a hydrographic survey carried out in 2014. Two another points of interest were also included on this research. On those spots, Brazilian warships reported potential navigation hazards while anchored in 2003 and 2005. It is worth mentioning, however, that these additional objects have never been detected in previous hydrographic surveys. At the end of this research, a joint analysis of the reference bathymetric data and the side scan sonar images obtained by AUV confirmed the presence of the objects loaded in the Bathymetric Database and those informed in Nautical Charts 1511 and 1512. This study provides a pathway for future uses of side scan sonar attached to AUV platforms in order to investigate cartographic representation of targets not identified by other methods.
Keywords: AUV (Autonomous Underwater Vehicle); hydrographic research; nautical charts; side scan sonar; submerged target